Tomosynthesis and mammography in evaluation of women with high breast density – Systematic review - Azevedo, Rita (2021)
Digital mammography is currently the pillar of the breast cancer screening program, however breast density negatively affects its diagnostic performance, decreasing its sensitivity due to the - so called in Radiology - “mask effect”. In order to overcome this inconvenience, tomosynthesis has achieved good results in women with high breast density, due to its ability to reduce false images resulting from overlapping tissues. This study aims to explore the literature regarding the integration of tomosynthesis in screening programs for the evaluation of women with high breast density, based on the clinical indicators: recall rate, false positive fraction (FPF) and detection of injuries. The literature search resulted in 79 studies, of which 11 were included for analysis. It appears that the use of tomosynthesis plus mammography is associated with the reduction in the recall rate, in all ACR categories, but mostly in category C (Starikov A. et al, 2016), reaching 8,83% for tomosynthesis and 10,98% for mammography (Alsheik N. et al, 2019), and 10,4% for tomosynthesis and 19,9% for mammography in the study by Conant E. et al, 2019. FPF also benefits from a decrease, however about 5 times higher in category D. The rate of lesion detection aldo increased with the adoption of tomosynthesis, being about 1,41 times higher in every 1000 women, and with greater expression in women with dense breast. It is concluded that the isolated use of tomosynthesis or its addition to mammography shows very positive results, since this imaging modality contributes to the detection of smaller lesions and, consequently, an increase in the detection rate of lesions, increased specificity, decrease in recall rate and FFP. For this reason, tomosynthesis proves to be a promising technique and can represent an effective response in screening programs.